Antonyms in English : construals, constructions and canonicity - Jones, Steven, 1974- (Cambridge, UK : Cambridge University Press, 2012)
'The study of antonyms (or'opposites') in a language can provide important insight into word meaning and discourse structures. This book provides an extensive investigation of antonyms in English and offers an innovative model of how we mentally organize concepts and how we perceive contrasts between them. The authors use corpus and experimental methods to build a theoretical picture of the antonym relation, its status in the mind and its construal in context. Evidence is drawn from natural antonym use in speech and writing, first-language antonym acquisition, and controlled elicitation and judgements of antonym pairs by native speakers. The book also proposes ways in which a greater knowledge of how antonyms work can be applied to the fields of language technology and lexicography'--
Machine generated contents note: 1. Antonymy and antonyms; 2. Antonyms in context; 3. Antonyms and canonicity; 4. Antonyms in acquisition; 5. Antonyms and negation; 6. Antonyms as constructions; 7. The cognitive construal account; 8. Conclusions -- looking backward, looking forward.
Includes bibliographical references and index.
Keywords: English language -- Synonyms and antonyms